Konsep Standar Halte dan Hentian Angkutan Perdesaan - Herawati, Herawati (Warta Penelitian Perhubungan, 2012)
Rural transportation system is far behind when compared with urban transportation which resulted in decrease of rural transport demand. Therefore, for increasing the rural transport demand is needed a standards and concepts of rural transport for improving transport services both in infrastructure and facilities. Bus stop for rural transport is One of the support facilities that no avilable. This standar involves a specific standard for rural transport. The study was conducted in Jember and District Kalianda. The method used in this study is a qualitative and quantitative analysis. Analyses were performed using standard guidelines stop I stops of public transport which will be further developed a standard stop for rural transport. The analysis is based on the major facilities and supporting public transport standards issued by the Directorate General of Land Transportation can not be met properly. In other hands, planning of bus stop is appropriate but layout of bus stops at the intersection is outside the specified minimum standards. To obtain the size of the standard concept of bus stop (length: 3m-5meter ), location of bus stops that have noticed the condition of the land use and supporting facilities of bus stop such as pedestrian markings should be provided.Keywords: rural, bus stop, rural transport Sistem transportasi perdesaan memang jauh ketinggalan jika dibanding dengan transportasi perkotaan yang berakibat pada kurang diminatinya angkutan perdesaan. Untuk itu diperlukan suatu standar-standar dan konsep peningkatan pelayanan angkutan perdesan baik dari sisi prasarana dan sarana maupun dari kompenen utama dan komponen penunjang. Salah satu fasilitas pendukung yang belum ada standarnya adalah halte dan tempat hentian untuk angkutan perdesaan. Untuk itu diperlukan suatu standar khusus untuk angkutan perdesaan. Penelitian dilakukan di Kabupaten ]ember dan Kabupaten Kalianda. Berdasarkan hasil analisis diperoleh bahwa fasilitas utama dan penunjang sesuai standar angkutan umum yang dikeluarkan oleh Ditjen Perhubungan Darat tidak dapat terpenuhi dengan baik sedangkan dari sisi perencanaan sudah sesuai kecuali letak halte dengan persimpangan masih diluar standar minimum yang telah ditentukan. Untuk konsep standar halte diperoleh ukuran halte (panjang 5 meter-3meter), lokasi halte yang telah memperhatikan kondisi tata guna lahan dan fasilitas pendukung halte seperti marka penyeberang jalan harus disediakan.Kata Kunci : perdesaan, halte, angkutan perdesaan